Penggunaan Buku Durus Al-Lughah Al-‘Arabiyyah dalam Pembelajaran Bahasa Arab di SDS IT - Priyana, Tsara Dwi; Lailazhizah, Cahyainda (Kalimatuna: Journal of Arabic Research, 2024)
This research aims to analyze the use of the book Duruss Al-Lughah Al-'Arabiyyah in SDS IT Risalatul Haq Cicadas. This research is descriptive research with a qualitative approach. Data was collected through observation, interviews and teaching practice. The subjects in this research were grade 3 students. Arabic language learning in this research emphasized the use of books in teaching and learning. The research results show that the direct method can be used as an effective learning method when learning Arabic. The advantage of direct media is that it makes it easier for students to understand and memorize the Arabic vocabulary conveyed by the teacher. A lot of students do not know the meaning of Arabic vocabulary.